Transformation of the labor market in Kazakhstan in the transition to a digital economy (Journal of Economic Research & Business Administration, 2019)
The modern world economy is moving to a new model of economic growth – the digital economy. In this process, the countries of the post-Soviet space are somewhat behind not only the developed, but individual countries of the average level of economic development (China, India). One of the reasons for the backlog is ignoring the continuity of labor and capital. Capital is not capable of sustainably developing without society fulfilling the adequate requirements of the labor market. Under these conditions, the integration of Kazakhstan into the international labor market can lead to imbalance in the labor force: the outflow of skilled workers abroad and the inflow of cheap, not educated labor force into the country.Effective use of labor potential is one of the most important tasks of the formation of a socially orientedstate, carried out within the framework of state policy in Kazakhstan. Therefore, the question of thetransformation of the labor market and raising the level of social security of the population is the mainagenda in the modern conditions of the development of the world economy.The purpose of the article is to identify changes in the labor market as a result of technological renewal,to identify the main directions of the transformation of the labor market in the digital economy.Research methods: used methods of comparative analysis, monitoring, identifying problems andfinding their solutions.The results of the study. On the basis of a review of changes in the labor market, the definition ofthe relationship between labor and capital, the role of an intellectual person has been revealed, a comparativeanalysis of the labor market «before» and «in the conditions» of the digital economy has beencarried out.